Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine whether the function [tex]\( f(x) = 3x^2 \)[/tex] is even or odd, we will use the definitions of even and odd functions.
1. Evaluating [tex]\( f(-x) \)[/tex]:
[tex]\[ f(-x) = 3(-x)^2 \][/tex]
Since [tex]\((-x)^2 = x^2\)[/tex], we have:
[tex]\[ f(-x) = 3x^2 \][/tex]
2. Checking the conditions for even and odd functions:
- A function is even if [tex]\( f(-x) = f(x) \)[/tex].
- A function is odd if [tex]\( f(-x) = -f(x) \)[/tex].
3. Comparing [tex]\( f(-x) \)[/tex] and [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 3x^2 \][/tex]
[tex]\[ f(-x) = 3x^2 \][/tex]
Since [tex]\( f(-x) = 3x^2 \)[/tex] and [tex]\( f(x) = 3x^2 \)[/tex], we have:
[tex]\[ f(-x) = f(x) \][/tex]
Thus, the function [tex]\( f(x) = 3x^2 \)[/tex] satisfies the condition for being an even function.
Conclusion:
- The function [tex]\( f(x) = 3x^2 \)[/tex] is even because [tex]\( f(-x) = f(x) \)[/tex].
So, the correct statement is:
- The function is even because [tex]\( f(-x) = f(x) \)[/tex].
1. Evaluating [tex]\( f(-x) \)[/tex]:
[tex]\[ f(-x) = 3(-x)^2 \][/tex]
Since [tex]\((-x)^2 = x^2\)[/tex], we have:
[tex]\[ f(-x) = 3x^2 \][/tex]
2. Checking the conditions for even and odd functions:
- A function is even if [tex]\( f(-x) = f(x) \)[/tex].
- A function is odd if [tex]\( f(-x) = -f(x) \)[/tex].
3. Comparing [tex]\( f(-x) \)[/tex] and [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 3x^2 \][/tex]
[tex]\[ f(-x) = 3x^2 \][/tex]
Since [tex]\( f(-x) = 3x^2 \)[/tex] and [tex]\( f(x) = 3x^2 \)[/tex], we have:
[tex]\[ f(-x) = f(x) \][/tex]
Thus, the function [tex]\( f(x) = 3x^2 \)[/tex] satisfies the condition for being an even function.
Conclusion:
- The function [tex]\( f(x) = 3x^2 \)[/tex] is even because [tex]\( f(-x) = f(x) \)[/tex].
So, the correct statement is:
- The function is even because [tex]\( f(-x) = f(x) \)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.